Efficiency of Electrical Energy in Building Base on DSM with AHP Method - Sunu Arsy Pratomo; Muhammad Haddin; Arief Marwanto (Journal of Telematics and Informatics, 2020)
In the modern world, electrical energy is very important to support all activities in office buildings, educational facilities, industrial complexes and household activities. The problem that occurs in the use of electricity is the lack of understanding of energy conservation from the consumer side. This causes the waste of electrical energy. An alternative solution to this problem is an effort to make efficient use of electrical energy from the consumer side. By applying Demand Side Management (DSM) to the building, an efficient and rational use of electrical energy is obtained. To implement DSM it is necessary to conduct an energy audit of the building. By conducting an energy audit then Energy Use Intensity (EUI) and the profile of electrical energy usage is obtained. After EUI and the energy use profile are known then energy policy recommendations are determined in the building. By using the Analytical Hierarchy Process (AHP) an alternative set of decisions is made that is right in reducing electricity consumption so that it reaches the desired efficiency point in accordance with building management policies The results of processing from AHP obtained an alternative set of electrical energy efficiency according to its weight is the regulation of the use of office facilities by 48.5%, maintenance of existing equipment by 31.1%, utilization of new energy-saving technologies by 20.4%. Keywords: Energy Audit, EUI, DSM, AHP.